Embodied performances of (post-)indenture: Creolization of Indian dance, music and nadrons in Guadeloupe - Sandrine Soukaï (Journal of Indentureship and its Legacies)
42,473 Indian indentured workers were transported to the French Caribbean archipelago of Guadeloupe between 1854 and 1889. Yet, until recently, the legacy of indenture was marginalized in public memory. The 1970s marked a turning point, with the emergence of Indianité , a French Caribbean cultural project aimed at valourizing the Indian components of the region’s culturally diverse and creolizing landscape. Drawing on still underdeveloped scholarship on Indianité , theories of creolization, studies on embodied memory of past trauma, I analyze how the descendants of Indian indentured labourers reconstruct and transmit the heritage and memory of indenture in Guadeloupe through embodied performances of Indian dance, music and, in particular, the danced and sung theatre known as nadrons (from Tamil nādagam ), formerly staged on plantations. My study interweaves close readings of Indo-Guadeloupean writer, cultural activist and politician Ernest Moutoussamy’s tryptic novel Marianne: fée de notre République du sang-mêlé ( Marianne: The Fairy of our Mixed-Blood Republic , 2018) and his poetry collection A la recherche de l’Inde perdue ( In Remembrance of Lost India , 2004) with interviews conducted with Guadeloupean Indian language and dance cultural associations. Combining an analysis of literary texts on the one hand, and cultural activists’ projects and experiences on the other, I tease out the paradoxes at the heart of Indian song and dance performances, demonstrating how they oscillate between a return to an ancestral Hindu India, a recognition of the creolization at work in French Caribbean Indianness and, more recently, an opening to the global Indian culture popularized by Bollywood.